Cryptosporidium spp. in domiciled dogs of the city of Lages, SC - Moura, Anderson Barbosa de; Teixeira, Everton Borba; Souza, Antonio Pereira de; Sartor, Amélia Aparecida; Bellato, Voldomiro; Stalliviere, Fernanda Magalhães (Revista de Ciências Agroveterinárias, 2009)
This work was carried out aiming to detect oocysts of Cryptosporidium spp. occurrence in fecal samples of dogs, to determine the point prevalence of infection and to evaluate the influence of risk factors for canine cryptosporidiosis. Fecal samples of 200 domiciled dogs were collected in the city of Lages, SC, Brazil. From each fecal sample, two smears were made and submitted to the modified technique of Ziehl-Neelsen stain. The samples were also submitted to centrifugalflotation with Sheather’s solution. Microscopy and micrometry were used in order to view and identify oocysts. Statistical analysis was performed by chisquare test ( ) to observe the relationship between positive animals and risk factors. Eight (4%) of the evaluated samples had the presence of Cryptosporidium spp. oocysts on the Ziehl-Neelsen technique. Three of them were also positive by the method of centrifugal-flotation. Animals fed with homely diet and maintained on environment with grass and/or soil showed higher positivity. The results indicate that dogs, due to their close interaction with humans, can also represent a source of infection of canine cryptosporidiosis, considered a recurrent zoonose disease by the World Health Organization.